Pembinaan Tata Bahasa melalui Kuis: Studi Evaluasi pada Peserta Didik Kelas V SDN Nyantong - Sabrina Fajriani Nuramali; Assyifa Rahman; Resha Zakiyatussolihah; Yuni Ertinawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the implementation of Indonesian grammar coaching through language quizzes and examine its effectiveness in improving the language skills of fifth-grade students at SDN Nyantong. The background of this study is based on the low ability of students to understand and use standard words, spelling, and punctuation in accordance with the applicable rules of Indonesian language. This condition requires more interesting, creative, and interactive learning innovations so that students are more motivated to learn grammar. The research method used is descriptive qualitative with data collection techniques through direct observation, interviews with teachers and students, and documentation of learning activities carried out in the classroom. The results showed that coaching activities through language quizzes increased students' activity, motivation, and interest in learning Indonesian. Through these activities, the learning process became more enjoyable and interactive, encouraging students to participate actively and express their opinions. Students showed a significant improvement in the correct use of standard words, spelling, and punctuation in both written and spoken contexts. However, there were still obstacles in the form of difficulties in distinguishing between standard and non-standard words and errors in the use of prepositions due to the influence of everyday language habits. Overall, language quizzes have proven to be an effective and relevant innovative learning strategy for improving Indonesian grammar skills in elementary schools.